Esophageal diameters in children correlated to body weight - Bott, Thomas; Kalle, Thekla von; Schilling, Alexander; Diez, Oliver Heinz; Besch, Sarah; Mehlig, Ulrike; Hetjens, Svetlana; Wessel, Lucas; Loff, Steffan (European journal of pediatric surgery, 2019)
Introduction The development of stenoses after correction of an esophageal atresia or acid and lye burn of the esophagus are well-known problems in pediatric surgery. Currently, stenoses are treated in the majority of cases by repeated balloon dilatations. The diameter of the balloons used is not standardized; standard curves do not exist. The aim of this study was to evaluate the diameter of the esophagus correlated to the body weight of the children as measured in upper gastrointestinal (GI) studies to answer the important question to what extent a stenosis should be dilated. Materials and Methods: Within the time period from 2011 through 2016, 60 patients with upper GI studies were selected. Evaluations were blinded to two different examiners. The diameters were measured under maximum contrast filling between the second and third rib (cranial point of measurement) and between the seventh and eighth rib (caudal point of measurement). For both, the anteroposterior and lateral aspect was examined. The diameter was calculated as the arithmetic average of both measurements within one level. The diameters were correlated to the weight of the children. Results: All children (n = 38) within the 3rd to 97th weight percentile were analyzed. Linear correlation and coefficients of 0.67 at the cranial point and 0.70 at the caudal point were found. Mean diameter at the cranial point of measurement was 6.75 mm at the lowest weight (2.6 kg) and 14 mm at 74 kg. Mean weight of these children (standard deviation [SD]) was 25.3 (18.8) kg and median age was 7 years. Within weight groups (0-10 kg; 10-20 kg; 20-35 kg; 35-50 kg; >50 kg), we calculated SD and two side tested critical 95% confidence interval for all measurements (n = 74). Conclusion: Although the variation in measurements is considerable, this evaluation gives a reliable hint to which extent esophageal stenoses should be dilated in relation to the body weight. To the best of our knowledge, this is the first investigation to evaluate the diameter of the esophagus in children in relation to the body weight.